Design and Implementation of a Hierarchically Interoperable Tag-Based File System using FUSE (PreTFS) - Lie Steven Staria Nugraha; Fahri Firdausillah (Journal of Information System and Informatics, 2026)
Traditional hierarchical file systems make semantic organization awkward: a file that naturally belongs to multiple contexts must be forced into a single directory, leaving users to choose an arbitrary location or rely on duplication, linking, or search. This paper presents the design, prototype, and evaluation of a file system that preserves conventional hierarchical standards while adding an opt-in, tag-based semantic layer for multi-context categorization. We describe (i) a design in which tags are represented as directories with reserved, prefixed names and tag intersections are expressed through ordinary path nesting, and (ii) a proof-of-concept implementation that validates feasibility in practice. The implementation, PreTFS, is built as a FUSE (Filesystem in User Space) file system and uses SQLite to store file metadata and content. Results show that the design is realizable and remains compatible with conventional applications and workflows without external tools or specialized APIs. Benchmarking against a native kernel file system (btrfs) reveals expected overheads from user-space indirection and metadata management, measuring approximately ~2–73 ms for metadata-oriented operations and ~1–160 ms for file-content operations. These costs indicate the approach is practical for small-scale environments such as personal information management, where semantic flexibility and interoperability can outweigh peak performance. The novelty lies in a simple, hierarchically interoperable tagging design that enables semantic categorization through standard directory navigation.